2019
DOI: 10.5114/bta.2019.83209
|View full text |Cite
|
Sign up to set email alerts
|

Production of indole acetic acid by Kocuria rosea VB1 and Arthrobacter luteolus VB2 under the influence of L-tryptophan and maize root exudates

Abstract: Phytohormones play a very important role in enhancing plant growth by direct or indirect mechanisms involving plant-microbe interactions. Indole acetic acid (IAA) is one of the key phytohormones that directly enhance plant development. Kocuria rosea VB1 (GenBank ID: KY608093.1) and Arthrobacter luteolus VB2 (GenBank ID: KY608094.1) from polluted industrial water samples were characterized through a biochemical assay, 16S rDNA sequencing, and for promoting plant growth abilities. IAA production by VB1 and VB2 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 28 publications
(34 reference statements)
1
1
0
Order By: Relevance
“…Furthermore, the significant differences in plant growth parameters between the PGPR treatments with and without L-TRP indicate that L-TRP supplementation strengthens the effectiveness of PGPR in promoting plant growth. These findings are consistent with previous studies by Karnwal (2019), which demonstrate that the addition of L-TRP enhances PGPR colonization in plant roots. This improved colonization allows PGPR to interact more effectively with plants, facilitating the exchange of nutrients, hormones, and other biochemical signals between the two organisms (Chandran et al, 2021;Kalitkiewicz & Kȩpczyńska, 2008;Pac ocirc me et al, 2016;Shahzad et al, 2022;Tsukanova et al, 2017).…”
Section: Resultssupporting
confidence: 93%
“…Furthermore, the significant differences in plant growth parameters between the PGPR treatments with and without L-TRP indicate that L-TRP supplementation strengthens the effectiveness of PGPR in promoting plant growth. These findings are consistent with previous studies by Karnwal (2019), which demonstrate that the addition of L-TRP enhances PGPR colonization in plant roots. This improved colonization allows PGPR to interact more effectively with plants, facilitating the exchange of nutrients, hormones, and other biochemical signals between the two organisms (Chandran et al, 2021;Kalitkiewicz & Kȩpczyńska, 2008;Pac ocirc me et al, 2016;Shahzad et al, 2022;Tsukanova et al, 2017).…”
Section: Resultssupporting
confidence: 93%
“…Chin-A-Woeng et al (2000) reported that the ability of Pseudomonas isolates to suppress disease relies mainly on their ability to colonise roots. The positive impact of PGPR is to foster the crop growth and yield (Karnwal 2019). Fatima et al (2009) also proved that seed germination rate, growth of roots and wheat shoot were increased by inoculating bacterial IAA and PGPR.…”
Section: Discussionmentioning
confidence: 99%